Beech forests (order Fagetalia sylvaticae Pawlowski 1928) in Serbia - Branko Karadžić (Botanica Serbica, 2018)
Beech forests occupy considerable areas in Serbia. The principal aims of this research were to detect variability patterns and determine biodiversity components in Serbian beech forests. The K-means clustering of a data set comprising 270 relevés and more than 500 species revealed seven ecologically interpretable groups of beech forests in Serbia. The groups are presented in a synoptic table, with calculation of diagnostic species. Canonical correspondence analysis indicates that the altitudinal gradient is the main factor affecting diversification of the investigated forests. Species richness and alpha diversity are greatest in beech forests of ravine habitats